A highly proton conductive membrane based on hydrolyzed NbCl5 and phytic acid. (21st May 2020) - Zhao, Ming-Yu; Wang, Yi-Di; Cheng, Dongming; Liu, Bai-Ling; Wang, Yong-Hui; Zang, Hong-Ying
Abstract: It is vital to choose economical and environmentally friendly proton conductive materials to improve the performance of proton exchange membranes, which occupies a unique position in proton exchange membrane fuel cells. This paper reports a new proton conductive nanocomposite, that was named NbO2 (OH)-PA prepared from phytic acid (PA) and NbCl5 . NbO2 (OH)-PA showed an excellent proton conductivity of 135 mS cm −1 at 85 °C and 97% relative humidity. In addition, NbO2 (OH)-PA was combined with sulfonated poly (ether ketone) (SPEEK) in different proportions to form proton conductive membranes, that are labeled SPEEK-x NbO2 (OH)-PA. SPEEK-0.9% NbO2 (OH)-PA exhibited the best proton conductivity of 0.17 S cm −1 at 80 °C in water. This work may provide new ideas for improving proton conductivity of membranes through simple methods. Graphical abstract: Economic and environmentally friendly phytic acid can be used in highly proton conductive materials and can be applied to proton exchange membranes. Image 1 Highlights: NbO2 (OH)-PA with highly proton conducivity was synthesis under mild conditions via sol-gel method. Green and environmentally friendly, cheap materials greatly reduce the cost of proton conductive materials. The doping of NbO2 (OH)-PA can effectively improve the proton conductivity of SPEEK membrane.